Augmented P2X response and immunolabeling in dorsal root ganglion neurons innervating skeletal muscle following femoral artery occlusion - Xing, Jihong (American Physiological Society, 2013)
The responsiveness of sensory neurons to muscle metabolites is altered under the conditions of insufficient limb blood supply in some diseases, such as peripheral artery disease. The purpose of this study was to examine ATP-induced current with activation of purinergic P2X subtypes P2X(3) and P2X(2/3) in dorsal root ganglion (DRG) neurons of control limbs and limbs with 24 h of femoral artery occlusion using whole cell patch-clamp methods. Also, dual-labeling immunohistochemistry was employed to determine existence of P2X(3) expression in DRG neurons of thin-fiber afferents. DRG neurons from 4- to 6-wk-old rats were labeled by injecting the fluorescence tracer DiI into the hindlimb muscles 4–5 days before the recording experiments. Transient (P2X(3)), mixed (P2X(3) and P2X(2/3)), and sustained (P2X(2/3)) current responses to α,β-methylene ATP (a P2X receptor agonist) are observed in small and medium DRG neurons, and size distribution of DRG neurons is similar in control and occluded limbs. However, the peak current amplitude of DRG neuron induced by stimulation of P2X(3) and/or P2X(2/3) is larger in occluded limbs than that in control limbs. Moreover, the percentage of DRG neurons with P2X(3) transient currents is greater after arterial occlusion compared with control. In addition, a rapid desensitization was observed in DRG neurons with transient currents, but not with sustained currents in control and occluded groups. Furthermore, results from immunofluorescence experiments show that femoral artery occlusion primarily augments P2X(3) expression within DRG neurons projecting C-fiber afferents. Overall, these findings suggest that 1) greater ATP-induced currents with activation of P2X(3) and P2X(2/3) are developed when hindlimb arterial blood supply is deficient under ischemic conditions and 2) increased P2X(3) expression is largely observed in C-fibers of DRG neurons after hindlimb vascular insufficiency.